2021
DOI: 10.1051/0004-6361/202039533
|View full text |Cite
|
Sign up to set email alerts
|

Radio observations of the merging galaxy cluster system Abell 3391-Abell 3395

Abstract: The pre-merging system of galaxy clusters Abell 3391-Abell 3395 located at a mean redshift of 0.053 has been observed at 1 GHz in an ASKAP/EMU Early Science observation as well as in X-rays with eROSITA. The projected separation of the X-ray peaks of the two clusters is ∼50 or ∼ 3.1 Mpc. Here we present an inventory of interesting radio sources in this field around this cluster merger. While the eROSITA observations provide clear indications of a bridge of thermal gas between the clusters, neither ASKAP nor MW… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 81 publications
3
43
1
Order By: Relevance
“…In a recent ASKAP observation covering 30 deg 2 centred on the Abell 3391/3395 galaxy cluster pair, and of comparable depth and angular resolution as the EMU-PS, Brüggen et al (2021) found the surface density of GRGs 1 Mpc to be ∼0.8 deg −2 , and that of GRGs 0.7 Mpc to be at least ∼1.7 deg −2 , suggesting that the EMU-PS should contain ∼200 and ∼460 such GRGs, respectively.…”
Section: Giant Radio Galaxiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent ASKAP observation covering 30 deg 2 centred on the Abell 3391/3395 galaxy cluster pair, and of comparable depth and angular resolution as the EMU-PS, Brüggen et al (2021) found the surface density of GRGs 1 Mpc to be ∼0.8 deg −2 , and that of GRGs 0.7 Mpc to be at least ∼1.7 deg −2 , suggesting that the EMU-PS should contain ∼200 and ∼460 such GRGs, respectively.…”
Section: Giant Radio Galaxiesmentioning
confidence: 98%
“…Early EMU/eROSITA results on the Abell 3391/95 galaxy cluster system (Reiprich et al 2021;Brüggen et al 2021) have already helped constrain physical processes in the merger. We show two additional examples of diffuse radio sources detected in the EMU-PS area in Figures 33 and 34.…”
Section: Clusters Of Galaxiesmentioning
confidence: 99%
“…All-sky Aitoff projection of the distribution of our newly discovered GRS in red, together with the GRS from six major published GRS lists, which are in black from [5], in orange from [15], in dark blue from [59], in dark green from [60], in dark magenta from [16], and in dark red from [46]. The thick blue line shows the area within |b| ≤ 2 • from the Galactic plane.…”
Section: Determination Of Radio Flux Densities and Luminositiesmentioning
confidence: 99%
“…The literature compilation of GRGs by [5] contains 223 objects larger than 1 Mpc, and after that, four further large samples of GRGs and one of GRQs were published. These contain (after correction of their LAS measures and exclusion of a few spurious objects consisting of separate sources) 68, 48, 18, and 25 GRS from [15,16,59,60] and 76 GRQs from [46]. This makes a total of 458 GRS published, neglecting here a few others that were reported in much smaller numbers in various papers, sometimes not even mentioning their GRS nature.…”
Section: Comparison Of Our Sample With Previously Published Grsmentioning
confidence: 99%
See 1 more Smart Citation